Tapping the Potential of the Molecular Genetic Expert Research of Objects of Animal Origin in the Fight against Their Illegal Trafficking - Sergei V. Aramilev; Viktoriya V. Gulevskaya; Georgii G. Omel’yanyuk; Anna A. Rybakova; Irina V. Storozhenko (Теория и практика судебной экспертизы, 2021)
Currently, the legal framework for protecting natural resources from human assault is being developed at the international level. However, the statistical data on the sentencing of persons convicted on the territory of the Russian Federation under Articles 258 and 258.1 of the Criminal Code of the Russian Federation in 2020 given in the article indicates: the crimes causing the reduction in the number of animal populations, and as a result, the loss of biodiversity, are challenging to prove; a small number of perpetrators are brought to criminal responsibility; punishment in the form of imprisonment is imposed only in isolated cases. However, using molecular genetic research methods for the biological material of wild animals, it is possible to fill in a significant part of the missing information or obtain new evidentiary information about the circumstances of crimes, including illegal hunting. The application of the DNA barcoding method, developed in the early 2000s, makes it possible to establish the taxonomic affiliation of living organisms when it is impossible to do this by classical methods, for example, if the organism is represented by a micro-number of biological tissues, and is also at the stages of the life cycle (egg, larva, embryo) with an insufficient number of morphological features. Thus, advanced DNA technologies allow us to obtain a considerable amount of previously inaccessible information.The issue of the illegal wild animal trafficking sold as “raised in captivity” is relevant for the pet industry and zoos and has implications both for animal welfare and the preservation of the natural environment. Methods based on the DNA analysis can also be applied for solving problems related to establishing the source of origin of the animal, in some cases – its habitat. The article provides cases from expert practice of ANO “Amur Tiger” when using molecular genetic methods of wild animal analysis allowed solving investigative and judicial tasks.